Does the satisfaction of psychological needs predict the development of life skills in dual-career athletes? - Melo, Sandro Victor Alves (2023)
The objective of this cross-sectional study was to investigate whether total need satisfaction and three separate basic psychological needs (autonomy, competence and relatedness) predict life skills development in dual-career athletes according to sex, type of sport, type of higher education institution and financial support. Participants included 136 Brazilian university athletes (65 boys and 71 girls) aged 17–23. Data collection was conducted via Basic Needs Satisfaction in Sport Scale (BNSSS) and the Life Skills Scale for Sport (LSSS). Bayesian multilevel linear regression model found that total need satisfaction and three separate basic psychological needs (autonomy, competence and relatedness) influenced life skills (teamwork, social skills, leadership, goal setting and communication) and total life skills development in dual-career athletes. Total need satisfaction influenced leadership and total life skills. Competence and relatedness influenced goal seating, social skill, leadership and total life skills. Autonomy might not have a strong correlation with life skills development dimensions standardised scores and total life skills standardised score independent of sex, type of sport, type of higher education institution and financial support. Based on such findings, satisfaction of all three basic needs combined (total need satisfaction) and separate autonomy, competence and relatedness was positively associated with the development of life skills in dual-career athletes.